Pengaruh Halal Knowledge dan Religiusitas terhadap Niat Membeli Produk Kosmetik Halal dengan Sikap Konsumen sebagai Mediasi - Nirmalasari, Nirmalasari; Sanurdi, Sanurdi (Prodi Hukum Ekonomi Syariah (Muamalah), 2025)
This study aims to analyze the influence of halal knowledge and religiosity on the purchase intention of halal cosmetic products, with consumer attitudes as a mediating variable. The research adopts a quantitative approach using the Partial Least Square (PLS) method to process data obtained from 150 respondents, consisting of students from the State Islamic University (UIN) Mataram in 2023. Respondents were selected based on the criteria of being halal cosmetic users, with data collected through both online and offline questionnaires. The results of the study indicate that halal knowledge has a positive and significant effect on purchase intention (t-statistic value of 3.786, p-value < 0.05). However, its effect on consumer attitudes is not significant (t-statistic value of 1.526, p-value > 0.05). On the other hand, religiosity is found to have a positive and significant influence on both consumer attitudes (t-statistic value of 2.331, p-value < 0.05) and purchase intention (t-statistic value of 3.334, p-value < 0.05). The study also reveals that consumer attitudes do not significantly mediate the influence of halal knowledge or religiosity on purchase intention.